Snakes and Ladders Game Media for Whole Number Counting Skills: Permainan Ular Tangga sebagai Media Pembelajaran untuk Mengembangkan Keterampilan Menghitung Bilangan Bulat - Amilda, Binta Naarah; Amir, Mohammad Faizal (Indonesian Journal of Education Methods Development, 2025)
General Background: Mastery of addition and subtraction of whole numbers forms the foundation of primary mathematics learning, yet many students experience difficulties when instruction remains abstract and disconnected from daily contexts. Specific Background: Game-based learning media provide concrete and engaging experiences that support young learners’ characteristics and participation. Knowledge Gap: Despite numerous studies on educational games, a structured development of a snakes and ladders medium specifically designed for whole number operations using a systematic instructional design model is still limited. Aims: This study aims to develop and produce a whole number snakes and ladders learning media product named ultabica for second-grade primary students. Results: Using a Research and Development approach with the ADDIE model, the study completed the analysis and design stages, identifying learning needs, mapping materials and student characteristics, and producing a colorful game board and guide containing contextual addition and subtraction tasks. The product facilitates concrete practice, collaborative play, and active engagement during learning activities. Novelty: The integration of structured arithmetic problems into a modified snakes and ladders board aligned with curriculum objectives provides a contextual and participatory instructional medium. Implications: The developed media serves as a practical reference for teachers to design interactive mathematics lessons that support counting skills through meaningful gameplay. Keywords: Learning Media, Snakes and Ladders, Whole Numbers, Game Based Learning, Primary Mathematics Key Findings Highlights: Produced a board game and guide aligned with curriculum targets Identified learner needs and content mapping through systematic analysis Facilitated collaborative and contextual arithmetic practice